A mixed-methods approach to investigating motivational regulation strategies and writing proficiency in English as a foreign language contexts. (February 2020) - Teng, Lin Sophie; Yuan, Rui Eric; Sun, Peijian Paul
Abstract: This empirical study used a mixed-methods approach to examining the relationship of writing proficiency levels and motivational regulation strategies in English as a foreign language (EFL) contexts. Data were collected from a total of 389 Chinese undergraduates through a writing task and a self-report questionnaire. Among the participants, 30 students from high writing-proficiency ( n = 15) and low writing proficiency ( n = 15) groups were invited to complete follow-up semi-structured interviews. Quantitative data of this study revealed that the high writing-proficiency students reported using more mastery and performance self-talk, interest enhancement, and emotional control than the low writing-proficiency students. Likewise, the semi-structured interviews indicated that the high writing-proficiency group demonstrated more maturity and flexibility in deploying some motivational regulation strategies (e.g., interest enhancement and mastery self-talk) while the low writing-proficiency group reported limited understanding and use of these strategies. In addition, knowledge about learning strategies, writing instruction, learning motivation, and academic self-efficacy were major factors affecting the use of motivational regulation strategies between the two proficiency groups.